Hubungan Self-Compassion Dengan Resiliensi Pada Anak Usia Sekolah - Remaja Di Panti Asuhan Anugerah Kasih Abadi Medan Estate - Simanullang, Rahael; Tambunan, Dior Manta (Universitas Murni Teguh, 2024)
Orphanage is a social institution that provides programs for the needs of the community, the phenomenon of problems that often occur in children in the form of negative emotions, such as feelings of lack of attention from caregivers which causes discomfort, tends to keep their problems to themselves, often feels sad when remembering the existence of parents and family who are far away or are already orphans, regulations that are too strict, and orphanages do not provide opportunities for their foster children to make their own decisions. The purpose of this study is the relationship between self-compassion and resilience in school-age children - adolescents at the Anugerah Kasih Abadi Medan Estate orphanage. This type of research is quantitative with a cross-sectional survey research design. The sampling technique in this study was Total Sampling and 56 respondents. Data analysis used the Pearson correlation parametric test. The results of this study indicate a significant relationship between Self-compassion and resilience with a p-value = 0.046 (α <0.05). It can be concluded that there isa relationship between self-compassion and resilience in school-age children - adolescents at the Anugerah Kasih Abadi Medan Estate orphanage. It is recommended for further researchers to add variables, social support, optimism, factors that support psychological well-being and individual ability to overcome difficulties.